2010
DOI: 10.1111/j.1600-0668.2010.00651.x
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of photocatalytic HEPA filter on microorganism removal

Abstract: The high efficiency particulate air filter is used widely to remove particulates and microorganisms from the air stream. However, the filter may become a source of microbes if those retained microorganisms proliferate and re-entrain back into the filtered air. This study demonstrates that such a problem can be handled effectively by using photocatalytic reactions to inactivate those confined microorganisms. A 60-100% microbe reduction can be achieved for a wide variety of microorganisms to provide better indoo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
68
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(72 citation statements)
references
References 28 publications
1
68
3
Order By: Relevance
“…1) were cut to a size of 20 × 20 cm. Before coating, the high grade filter was pre-treated to remove water-resistance by washing with 0.08 M sodium dodecyl sulfate, drying at room temperature for 24 hr and desiccating for at least 2 hr (Chuaybamroong et al, 2010).…”
Section: Tio 2 -Coating Proceduresmentioning
confidence: 99%
“…1) were cut to a size of 20 × 20 cm. Before coating, the high grade filter was pre-treated to remove water-resistance by washing with 0.08 M sodium dodecyl sulfate, drying at room temperature for 24 hr and desiccating for at least 2 hr (Chuaybamroong et al, 2010).…”
Section: Tio 2 -Coating Proceduresmentioning
confidence: 99%
“…Baking at 50°C for 30 min after coating with 5% TiO 2 not only yielded higher loading than baking at 100°C for 30 min, but these air filters also achieved greater strength, resulting in a more practical use for air treatment. Moreover, this baking method after coating produced better energy-saving air filters than the previous studies 6,16,17 . When comparing 2% and 5% TiO 2 loading after baking at 50°C for 30 min, the highest loading was achieved by coating with 5% TiO 2 .…”
Section: Discussionmentioning
confidence: 59%
“…This result was consistent with a previous study 20 which found that this chemical surface treatment provided not only increased roughness of the fibre surfaces but also increased the interaction between the TiO 2 and the substrate. According to the previous investigations 16,17 , using 0.08 M SDS could reduce the water resistance of the fibres of the pretreated HEPA filters, which were the same type of HEPA filter used in this study. In the present experiment, some fibres and other wastes were found in the SDS suspension, and these wastes also changed the colour of the suspension.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…Typical catalysts include TiO 2 , WO 3 , ZnS, while the photocatalytic reaction can be achieved with fluorescent or UV light. Combination PCO/HEPA filter units have been proposed to purify the indoor air [36]. Pathogens have been observed to be readily destroyed by PCO units [37], however most research into PCO cleaner for indoor air purification have been trialled in laboratory settings, and there is little information available on its efficiency in a biodefense setting environment.…”
mentioning
confidence: 99%